PENGARUH TITANIUM DALAM LAPISAN LAS TERHADAP STRUKTUR MAKRO-MIKRO, KEKERASAN, DAN LAJU KOROSI: Titanium Effect in Weld Layer on The Macro-microstructure, Hardness, and Corrosion Rate - Sopiyan; Syaripuddin; Muhammad Hafidz Fatahillah; Muhammad Fauzan Perdana Putra; Muhammad Yunan Hasbi (Universitas Negeri Jakarta, 2024)
Low carbon steel cannot be hardened because of its low carbon content. Therefore, a hardfacing process is carried out to increase hardness. Apart from increasing hardness, the benefits of hardfacing can increase wear and corrosion resistance. The hardfacing process using the shielded metal arc welding (SMAW) process generally uses commercial electrodes. Therefore, it is necessary to add other elements such as titanium (Ti) to the weld layer to further increase its hardness. This research aims to study the influences of Titanium (Ti) addition in welding layers that were welded using HV 600 to micro and macrostructure, hardness, and corrosion rate. The hardfacing was conducted using the SMAW process with the various addition of Ti (0.115, 0.223, and 0.334 g) and cooled at room temperature. Macrostructure and microstructure were investigated using digital cameras and an optical microscope. Hardness and corrosion rate were investigated using the Vickers hardness test and weigh loss method. Based on macrostructure investigation, there is a perfect fusion between base metal and weld metal. The microstructure formed is a austenite, martensite and carbide phase. The lowest corrosion rate of 17.54 mpy was seen in the Ti1 sample. The lowest Ti addition would resulting higher hardness at 761.06 VHN.